Rancho San Ignacio (1920)
The Adelaide Road entrance to the ranch of Ignacy Jan Paderewski, Polish pianist and politician. This specific property produced walnuts and almonds, and served as a short cut to Merit Springs. Paderewski was also a noted grower of Petite Sirah and Zinfandel grapes. His wines went on to win awards and establish Paso Robles' reputation for wine production before Prohibition.